The Influence of Online Learning on Students' Learning Motivation in Study Design and Forming Technology Automotive Body - Yuga Nugraha; Yusep Sukrawan; Ibnu Mubarak (VANOS Journal of Mechanical Engineering Education, 2024)
The purpose of this study in general is to find out whether there is a causal relationship or influence on online learning on students' learning motivation in the Automotive Body Design and Formation Technology course. The method used is quantitative method, this method only to find out the results of the research is numeric then inferred using annotations. The population in this study were students of the Department of Mechanical Engineering Education, automotive concentration, class of 2018 who had taken online lectures on automotive body technology design and formation, so a sample of 30 people was obtained. The research instrument based on the variable is online learning as the independent variable and motivational variables as its dependent variable. This study uses a simple linear regression testing to see t counted to determine whether there is a causal link or influence in a linear manner. Based on the results of the study, it can be concluded that there is a significant positive effect between online learning on student learning motivation, with an influence value of 43.1% in large category.